Robotic Assisted Total Hysterectomy: the First Experience - Šiaulys, Raimondas (Lietuvos chirurgija, 2019)
[full article and abstract in Lithuanian; abstract in English] We analyzed 23 cases of robotic assisted total hysterectomy performed in Klaipėda university hospital using Senhance® robotic system. Patients were operated on using Senhance® robotic system for endometrial cancer, myomatosis, endometriosis, prophylacticaly after breast cancer treatment, single cases for cervical pathology and benign tumor of ovary. Surgical technique and results are discussed. Conclusion.Robotic assisted total hysterectomy is a safe method for patient and comfortable for the surgeon.